Miskonsepsi Siswa Dalam Bidang Studi Kimia: - Sabekti, Ardi Widhia (Jurnal Zarah, 2015)
Formal thinking, memorize, mathematical operation, visuospatial, and multiple representations (MRs) abilities are required in studying chemistry. Various abilities required in studying chemistry makes chemistry being a difficult subject to study. This difficulty may induce incorrect understanding when occurs consistently may lead to a misconception. The other sources of studentâs misconception are internal factors of students such as daily life experience and external factors such as textbooks, media, language, and school instruction.